2007
DOI: 10.1002/ijc.22742
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term population‐based marriage rates among adult survivors of childhood cancer in Britain

Abstract: The objectives of this study were to assess the number of adult survivors of childhood cancer who ever married and the factors influencing marriage, compare observed marriages to those expected from the general population, and assess age at marriage and influencing factors. The data is based on the British Childhood Cancer Survivor Study (BCCSS), which is a populationbased cohort of 18,119 individuals who were diagnosed with childhood cancer between 1940 and 91 and survived at least 5 years. Fourteen thousand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
73
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 20 publications
9
73
2
1
Order By: Relevance
“…Whereas skin cancer in both men and women results in elevated marriage rates, brain cancer has a negative impact only in women. This is in contrast to the findings of others [7,8]. Breast and testicular cancer are gender-specific cancer types, closely connected to sexuality and reproduction.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Whereas skin cancer in both men and women results in elevated marriage rates, brain cancer has a negative impact only in women. This is in contrast to the findings of others [7,8]. Breast and testicular cancer are gender-specific cancer types, closely connected to sexuality and reproduction.…”
Section: Discussioncontrasting
confidence: 90%
“…Cancer in women thus appears to be more harmful for marriage formation than cancer in men, but is mainly a consequence of the strong negative impact of female childhood cancer. This gender difference is disproportionate to findings in some larger childhood cancer studies [7,8,10,15], but not all [16,37]. The effects of the various cancer types are surprisingly inconsistent.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Byrne et al 1989;Pastore et al 2001;Rauck et al 1999;Frobisher et al 2007). In relation to childhood cancer, it has been suggested that fertility concerns might impact relationship formation; however analysis of the British Childhood Cancer Survivor Study (Frobisher et al 2007) did not support this.…”
Section: Contextmentioning
confidence: 99%
“…The impact of cancer on marriage rates has mainly been studied for survivors of childhood cancers, and most studies show slightly reduced marriage rates after cancer, ranging from around 5-20% for men and women [7][8][9][10][11][12][13][14]. In a recently published study, marriage rates among young Norwegian cancer survivors were shown to have become similar to those of the general population with time, although breast and female brain cancer remained associated with reduced rates [15].…”
Section: Introductionmentioning
confidence: 99%